Portfolio Inflows and Real Effective Exchange Rates : Does the Sectorization Matter? - Ouedraogo, Rasmane (IMF Working Papers; Working Paper ;, 2017)
It has been well-established in the literature that portfolio inflows appreciate the real effective exchange rate. However, the literature lacks a systematic empirical analysis of the impact of portfolio inflows by institutional sector or borrower type. This paper fills this gap by exploring the impact of the inflows of portfolio capital into three institutional sectors (government, banks and corporates) on the real effective exchange rate. Using a large sample of 73 countries, it shows that the effect of portfolio inflows on the real effective exchange rate depends on the sector the investment flows inches The findings are robust to different econometric methods, additional variables in the model, and various indicators of real effective exchange rates.